Research as development biomedical research, ethics, and collaboration in Sri Lanka - Sariola, Salla; Simpson, Bob 1956- (Cornell University Press, 2019)
"Shows how international biomedical researchers in Sri Lanka work across cultural, epistemic, economic, and power differences to accomplish clinical trials"...
Includes bibliographical references and index
Keywords: Medicine -- Research -- Sri Lanka; Medicine -- Research -- International cooperation; Clinical trials -- Moral and ethical aspects -- Sri Lanka; Medical ethics -- Sri Lanka; Bioethics -- Sri Lanka; Medical economics -- Sri Lanka; Randomisierter Test; Klinisches Experiment; Medizinsoziologie; Biomedizin; Anthropologische Medizin; Wissenschaftliche Kooperation; Bioethik; Sri Lanka